Evoluzione dell'edificato residenziale in rapporto alla pericolosità sismica (GEOmedia, 2015)
Census data at the enumeration area level can help us to understand some essential aspects about residential building, in particular, in a Country where the portion of buildings demolished and rebuilt is almost nothing, the variable time of construction provides the dimension of the urban sprawl. This information was compared with national seismic hazard map, developed by National Institute of Geophysics and Volcanology (INGV), to assess the evolution of the residential building compared to natural phenomena such as seismic events.The comparison between various types of information was carry out using GIS software, in particular "overlay" functions allows us to assign to each enumeration area the level of seismic hazard. Moreover, the use of microdata at the enumeration area level, it allows the calculation of the vulnerability indicators, grouped by time of construction and by population density, in seismic hazard classes at the municipal level.